Structural, functional, and evolutionary relationships between λ-exonuclease and the type II restriction endonucleases - Kovall, Rhett A. (The National Academy of Sciences, 1998)
λ-exonuclease participates in DNA recombination and repair. It binds a free end of double-stranded DNA and degrades one strand in the 5′ to 3′ direction. The primary sequence does not appear to be related to any other protein, but the crystal structure shows part of λ-exonuclease to be similar to the type II restriction endonucleases PvuII and EcoRV. There is also a weaker correspondence with EcoRI, BamHI, and Cfr10I. The structure comparisons not only suggest that these enzymes all share a similar catalytic mechanism and a common structural ancestor but also provide strong evidence that the toroidal structure of λ-exonuclease encircles its DNA substrate during hydrolysis.